PENDAPATAN MASYARAKAT PETANI PENYADAP KARET DI TEMBAWANG DI DESA BANUA TENGAH KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Kurniason, Melki; Fahrizal, Fahrizal; Roslinda, Emi (JURNAL HUTAN LESTARI, 2019)
Rubber is a forestry plant producing sap. Rubber latex is needed for various industrial purposes. Rubber is a side business as well as additional income for the community besides farming in Banua Tengah Village. The method used is a survey method with interview techniques. Sampling was done intentionally (purposive sampling). The number of samples taken was 61 respondents who were ; rubber farmers, married, worked tapping rubber and owning rubber plantations. Data analysis consists of calculating total income and multiple linear regression analysis. The analysis results obtained total income / Tr received by farmers around Rp. 390,000 - Rp. 2,840,500 / month, when compared to the UMR established by the Government in 2018, UMR Kapuas Hulu Regency is Rp. 2,204,650.00 / month, there are 2 (two) farmers who have an income above the minimum wage while 59 other farmers are still under the UMR There are four factors that influence the income of rubber farmers in Desa Banua Tengah namely land area, work experience, rubber age and workdays, of the four most influential factors are land area and workday variables, while the work experience and rubber age variables are not very influential. Factors of land area, work experience, rubber age and working days together greatly affect farmers' incomes with the equation of total income of rubber farmers as follows: ln Y = Â 9,817 +Â  0,397 ln X1 + 0,098 ln X2 + 0,061 ln X3 + 1,194 ln X4 Correlation value R = 0.928 and the value of determination R2 = 0.861 From these equations obtained a constant value of 9,817 which shows that income from rubber farmers (Å¶) in Desa Banua Tengah is Rp. 9,817 if Xâ‚, Xâ‚‚, X3 and X4 are considered zero. Å¶ is positively correlated with Xâ‚, Xâ‚‚, X3 and X4.Keywords: Influential factors, Latex, Rubber farmers, Total income